2013
DOI: 10.1002/bjs.9021
|View full text |Cite
|
Sign up to set email alerts
|

c-Kit expression as a prognostic molecular marker in patients with basal-like breast cancer

Abstract: c-Kit might be a prognostic marker and possible molecular target for therapy in patients with BLBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 30 publications
(46 reference statements)
2
44
0
Order By: Relevance
“…Immunohistochemical studies were performed as previously described on core needle biopsy specimens [18, 19]. Tumor specimens were fixed in 10% formaldehyde solution and embedded in paraffin, and 4-μm-thick sections were mounted on glass slides.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical studies were performed as previously described on core needle biopsy specimens [18, 19]. Tumor specimens were fixed in 10% formaldehyde solution and embedded in paraffin, and 4-μm-thick sections were mounted on glass slides.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown varying results; Nielsen et al , 2004 reported no difference in survival for c-KIT positive BLBC patients compared to control [40], whereas Kashiwagi et al , 2012 found a poorer outcome for c-KIT positive BLBC patients with a hazard ratio of 2.29 [26]. One explanation for these opposing results is differences in cut-point for categorizing a sample as positive; Nielsen et al , 2004 used ≥25% stained cells as cut-point while Kashiwagi et al , 2012 set their limit to ≥10%.…”
Section: Discussionmentioning
confidence: 99%
“…The 93 primary tumors and the metastatic lesions in the lymph nodes from 57 patients were immunohistochemically stained as described previously (28). Briefly, the specimens were fixed in 10% formaldehyde solution and embedded in paraffin.…”
Section: Patientsmentioning
confidence: 99%